Evaluation of resistance mechanisms of mulberry cultivars through component analysis of aecial infection cycle of mulberry red rust (Aecidium mori) - and OSCAR S. OPINA, ANGELINA T. GONZALES* (Indian Phytopathology, 2013)
Component analysis of resistance showed that the resistant reaction conferred by resistant cultivars was attributed to its ability to limit or suppress sporulation capacity, prolong latent period and shorten the infectious period of the fungus. The cohort life statistics revealed that the survival rate, proportion of infection units of Aecidium mori Barclay at various infection states and infection efficiency of mulberry red rust (MRR) did not vary significantly among resistant (Alfonso), moderately resistant (S-13 and SRDC-2) and susceptible (M-local, S-54, S-61 and Batac) mulberry cultivars. Regardless of cultivar, high mortality of infection units was recorded during the early stages of infection process. Sporulation capacity, infectious period and latent period of A. mori significantly differed among resistant, moderately resistant and susceptible cultivars. The infectious period of A. mori on susceptible cultivars was longer (20-32 days) compared to moderately resistant (12-28 days) and resistant (10 days) cultivars. A. mori produced abundant aeciospores in susceptible cultivars, few to less abundant in moderately resistant cultivars and very few in resistant cultivar. The latent period is longer in resistant cultivar compared with susceptible cultivars. The observed resistant reaction cv. Alfonso can be attributed to its ability to limit or suppress sporulation capacity, prolong latent period and shortened infectious period of the fungus.